Analysis and Design: Accounting Information System in Purchasing and Supplying - Noerlina Noerlina; Johan Johan; Yuliana Yoswara (CommIT (Communication and Information Technology) Journal, 2011)
The purpose of the research are the purchase and material supply process are the main process of the company and it will determine the operational company, so it needs an accounting information system to help them in the planning and taking the best decision. Research methods used are data and information collected which using the analysis and design method. This method needs to support the design of accounting information system in the company. The result are there’s still any weaknesses happened that will hamper the operational company.Index Terms - Analysis and Design, Accounting Information System, Purchasing, Supply.